2019
DOI: 10.1088/1367-2630/ab2489
|View full text |Cite
|
Sign up to set email alerts
|

A minimal tight-binding model for the quasi-one-dimensional superconductor K2Cr3As3

Abstract: We present a systematic derivation of a minimal five-band tight-binding model for the description of the electronic structure of the recently discovered quasi-one-dimensional superconductor K 2 Cr 3 As 3 . Taking as a reference the density-functional theory (DFT) calculation, we use the outcome of a Löwdin procedure to refine a Wannier projection and fully exploit the predominant weight at the Fermi level of the states having the same symmetry of the crystal structure. Such states are described in terms of fiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…On the side of materials, we point out that there exists a long list of quasi 1D systems that have already shown experimental fingerprints of spin-triplet superconducting pairing and appear as prominent building blocks for fabricating the proposed hybrid devices. For instance, this is the case for the organic Bechgaard salts [88,89], the purple molybdenum bronze Li 0.9 Mo 6 O 17 [90], and more recently the Cr-based pnictide superconductors [91,92]. Moreover, we remark that the design of spinful triplet superconductivity can also rely on harnessing the orbital degrees of freedom, as it has been demonstrated for 2D electron gases [103] and multi-orbital optical-lattice systems exhibiting superfluidity [104].…”
Section: Magnetic Field Configurationmentioning
confidence: 65%
See 1 more Smart Citation
“…On the side of materials, we point out that there exists a long list of quasi 1D systems that have already shown experimental fingerprints of spin-triplet superconducting pairing and appear as prominent building blocks for fabricating the proposed hybrid devices. For instance, this is the case for the organic Bechgaard salts [88,89], the purple molybdenum bronze Li 0.9 Mo 6 O 17 [90], and more recently the Cr-based pnictide superconductors [91,92]. Moreover, we remark that the design of spinful triplet superconductivity can also rely on harnessing the orbital degrees of freedom, as it has been demonstrated for 2D electron gases [103] and multi-orbital optical-lattice systems exhibiting superfluidity [104].…”
Section: Magnetic Field Configurationmentioning
confidence: 65%
“…Interestingly, in some of these experiments [68, 71-73, 79, 83], spin-polarized scanning tunneling microscopy (STM) emerged as a powerful tool to detect MBSs by means of the elecronic spin polarization they induce [84][85][86][87]. Nonetheless, such a detection strategy has not yet been pursued to confirm intrinsic p-wave superconductivity in prominent candidate materials, e.g., the Bechgaard salts [88,89], lithium molybdenum purple bronze [90], and more recently in the Cr-based pnictide K 2 Cr 3 As 3 [91,92].…”
Section: Introductionmentioning
confidence: 99%
“…Although many interesting studies have been so far reported on these and other similar compounds, both theoretical [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and experimental [26][27][28][29][30][31][32][33][34][35][36], only a limited amount of information on WP single crystal system is until now available [8]. The aim of this paper is to give a contribution to the investigation of the properties of WP compound, providing electronic structure calculations and a consistent description of resistivity measurements from experiments carried out on WP single crystal samples.…”
Section: Introductionmentioning
confidence: 99%
“…Although spin-triplet pairing is less common than the conventional spin-singlet one, experimental observations in the last decades have gathered many evidences for spintriplet superconductivity in a large variety of materials, such as heavy-fermion compounds [31][32][33], noncentrosymmetric materials [34,35], organic conductors [36][37][38], layered oxides [39], doped topological insulators [40], and more recently in the Cr-based pnictide K 2 Cr 3 As 3 [41,42]. In addition to intrinsic materials, artificial spin-triplet SCs can be engineered in a large variety of quantum-material and -device platforms based on conventional spin-singlet pairing.…”
Section: Introductionmentioning
confidence: 99%